(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
A patient may have access to one or more healthcare organizations, meaning that their health information is spread across separate EHR systems, resulting in data fragmentation. Thus, the medical history of a patient may not be complete, consistent or comprehensive if the records cannot be combined into a single consistent overview that may not be efficient for the future diagnosis of the patient. Health Information Exchange (HIE) relates to the electronic transfer of health care information between institutions and practitioners within a specific group, region or hospital. However, HIE is surrounded with various challenges such as data insecurity, threat to patient privacy, dependency on third parties and so on. Blockchain through its characteristics such as safety, privacy, decentralization, and immutability has the ability to transform health care, putting the patient at the core of the health care ecosystem, and enhancing health data security, privacy, and interoperability thereby offering HIE with excellent potential. In this paper Health Information Exchange (HIE) and Blockchain Technology are discussed and the possibility of using blockchain technology to achieve HIE is presented.